Exploring the Complexity of First-Year Student Belonging in Higher Education : Familiarity, Interpersonal, and Academic Belonging. - Kahu, Ella R.; Ashley, Nicole; Picton, Catherine (Student Success v.13 n.2 p.10-20 https://doi.org/10.5204/ssj.2264, 2022)
Belonging is critical to first-year student success and persistence in higher education. However, differing definitions make it challenging to fully understand why belonging is significant. Foregrounding student voice, this research explored how first-year Australian university students talked about their belonging. Using Kahu and Nelson’s (2018) framework of student engagement as a lens, 18 students were interviewed weekly throughout the year. Students talked about belonging in three distinct but interrelated ways: familiarity, interpersonal belonging, and academic belonging. While all were important for student wellbeing and engagement, academic belonging, students’ sense that university, their discipline, and courses were “right” for them, was critical for perseverance. Unlike interpersonal belonging which tended to build through the year, academic belonging fluctuated for many students. The findings suggest framing belonging merely as about relationships limits understanding of this important construct. Contributing to scholarship by bringing a refreshed perspective to the nuances and complexity of belonging, the research suggests higher education providers need to monitor and foster academic belonging in first-year students. [Abstract, ed]